Potent effects of dioscin against thioacetamide-induced liver fibrosis through attenuating oxidative stress in turn inhibiting inflammation, TGF-β/Smad and MAPK signaling pathways. (June 2015) - Zhang, Xiaoling; Xu, Youwei; Qi, Yan; Han, Xu; Yin, Lianhong; Xu, Lina; Liu, Kexin; Peng, Jinyong
Highlights: Dioscin significantly suppressed the proliferation of HSC-T6 cells. Dioscin showed potent effect against TAA-induced liver fibrosis in rats. Dioscin showed anti-oxidative and anti-inflammatory effects. Dioscin effectively facilitated matrix degradation. Dioscin markedly inhibited TGF-β/Smad and MAPK signaling pathways. Abstract: The protective effects and mechanisms of dioscin against liver fibrosis were investigated. The results showed that dioscin markedly suppressed the proliferation of HSC-T6 cells, but not to the isolated hepatocytes, down-regulated the levels of fibronectin, α-SMA, collagen and vimentin, and up-regulated PPAR-γ expression to inhibit HSC activation. Interestingly, dioscin also significantly rehabilitated the levels of body weights, AST, ALT and hydroxyproline in rats caused by TAA, which were verified by histological determinations. Mechanistically, dioscin obviously facilitated matrix degradation, significantly decreased liver inflammation by inhibiting NF-κB activation and proinflammatory cytokine production, attenuated oxidative stress by reducing lipid peroxidation and activating Nrf2-mediated antioxidantive enzymes, and evidently adjusted TGF-β/smad and MAPK signaling pathways. In conclusion, dioscin ameliorated liver fibrosis via affecting oxidative stress, inflammation, HSC activation, matrix degradation, TGF-β/smad and MAPK pathways, which should be developed to be one effective food and healthcare product for the treatment of liver fibrosis in the future.